2 - Better infection than hunger’. A study of illness perceptions with special focus on urinary schistosomiasis in Northern Tanzania - Beth Maina Ahlberg,; Rose Mwangi,; Gabriel Poggensee,; Hermann Feldmeier H,; Ingela Krantz, (African Sociological Review, 2003)
This paper is about how a community in Northern Tanzania experiences and reasons around urinary schistosomiasis and more specifically female genital schistosomiasis or schistosomiasis of the reproductive tract. As a disease, female genital schistosomiasis presents itself with a variety of symptoms which neither the affected woman nor the medical professionals usually recognise as schistosomiasis. The study therefore focused on symptom recognition, the question being whether women living in an endemic area can distinguish symptoms of urinary and genital schistosomiasis from those of other diseases presenting in similar ways. Data were generated using a combination of qualitative methods including observation, individual interviews and focus group discussions with diverse categories of people. All the research participants were aware of the link between water and infection. Because the disease is associated with farming, the main livelihood, there was a strong feeling among the research participants that treatment, whether in hospital or by traditional medicine could not effect permanent cure. Re-infection was considered inevitable and as schistosomiasis was said to be less poisonous than malaria, it was felt there was little choice between being infected and having food. Making sense of the symptoms was considered moreover difficult although women and men said they could tell whether blood in urine was due to urinary schistosomiasis or other conditions such as sexually transmitted diseases which present similar symptoms. The similarity of symptoms was said to be problematic also because of the sensitivity and stigma in sexually transmitted diseases. Urinary schistosomiasis is therefore a complex health problem and for any effective control there is clearly a need to grasp this complexity.